BUSINESS ANALYSIS OF PURSE SEINE IN CV. IDOLA GROUP WATERS OF SASAK SASAK RANAH PASISIE SUB-DISTICT WEST PASAMAN REGENCY WEST SUMATERAPROVINCE - Muhammad Syawal; Zulkarnaini Zulkarnaini; Hendrik Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in CV. Sasak Waters Idol Group Sasak Ranah Pasisie sub- District, West Pasaman Regency, West Sumatra Province. The purpose of this study are (1) To find out the income of fishing business using purse seine in the waters of Pasisie realm. (2) How the feasibility of catching businesses using trawl fishing gear is seen from the investment criteria and NPV (net preset value) business analysis, BCR (benefit cost ration), IRR (internal rate of ration) in Sasak pasisie realm waters. (3) Analyzing the sensitivity of 45 GT vessels viewed from investment criteria (NVP, BCR, and IRR) if there is an increase in variable costs and decreased revenue. The results of this study are that the fishing gear business in CV. The Idola Group can be concluded that (1) the total investment of 45 GT Trawl Ring business is IDR 1,275,185,000. As for the annual revenue of the 45 GT fleet of 119,550 kg.(2) Based on the investment criteria the NPV value of the Trawl Ring fishing gear business measuring 45 GT is IDR 1,448,809,360, BCR is 1.23 and IRR is 86.03% for 10 years of business. (3) Based on the sensitivity analysis carried out by the Trawler ring measuring 45 GT with the Revenue scenario model down 10% and the cost is assumed to be a fixed NPV ofIDR 666,409,360, BCR of 1.10, and an IRR of 86.03%, then an increase in cost of 10% is assumed to be fixed NPV of IDR 811,290,296, BCR of 1.12, IRR of 86.03.Keywords : Business Analysis. Purse Seine. CV. Idola Group. Sub-District Sasak Ranah Pesisie